Pedological and taxonomical research of Indian tropical soils for fulfilling the UN SDGs: Current status and the future scope - D.K. Pal; Ashim Datta; D. Vasu; Ranjan Paul; K. Karthikeyan; Pramod Tiwary (Soil Security)
The tropical soils of the world including India have hardly been considered as a viable substrate for successful agriculture. Although ample research in India has been conducted but sustaining their productivity is a challenge for the land managers. To fulfil this challenge, acquiring new knowledge through soil care programmes become mandatory. Without such initiative, any attempt to bridge the disparity between food production and future population will be an uphill task. Realizing this urgency, during the last few decades, Indian pedologists and edaphologists took up research endeavours on the pedological and taxonomical nuances and subtilities on benchmark (BM) and identified large number of soil series. The main purpose was to provide a “carrier of information” of the major soil orders (Inceptisols, Mollisols, Alfisols, Ultisols, and Vertisols) of tropical India. Based on this, scientists developed a current status on soil health, greenhouse gas emissions and soil degradation and resilience. We explicitly reviewed these research endeavours on Indian tropical soils for fulfilling the United Nations Sustainable Developments Goals (UN SDGs). This information may possibly remove the long-standing misgivings about positive pedological functionalities, which may prove the Indian tropical soils as one of the important contributors in strengthening India's economic status. This status of Indian tropical soils, however, still needs to be worked out to establish a relationship between soil properties and ecosystem services at a larger scale, while accomplishing the UNSDGs for increasing crop productivity and sustaining soil and human wellbeing in Indian agricultural soils in the immediate future and beyond.